DIPLOMASI INDONESIA DALAM PENANGANAN KONFLIK ROHINGYA 2013-2017 - Rara Zulfa; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This Research aimed to explain Indonesian Diplomacy pevention to Rohingya conflict in 2013-2017. The pronolonged etnicity conflict in Rohingya made Indonesian Government and Inonesian Society took a step to handle this conflict. With various powerful news about this conflict where ethnic Rohingya were tortured in daily basis caused international would gave more respons to this conflict. Indonesian as an ASEAN country uphold world justice certainly performed some efforts to overcome this conflict. Indonesian as a neighboring country of Myanmar and has some closeness of several things tried hard to do approach in order to perfomed prevention of this conflict.This research used Neorealism prespective. Neorealism assumes that all world problematic can be solved by working together. If it connected to neorealism, Indonesian entered the Myanmar International Anarchy System. Furthermore, Indonesian, Myanmar and International NGO pulled together to give human aids to Rohingya society. In addition, this research was support by diplomacy theory in which the writer used Multi Track Diplomacy and choose three tracks for this research, there are : Track 1 Goverment, track 2 NGO, and track 9 media. level of analysis that was being used was Analysis of nation state. The writer used qualitative method and data collection of interview and literature study.This research showed Indonesia’s diplomacy which used human aids to overcome the conflict of rohingya ethnic in Myanmar using Track 1 of Government, Track 2 of NGO, and Track 9 of MediaKeywords: Conflict, Rohingya Ethnic, Diplomacy, Multi-Track Diplomacy